Harnessing perennial and indeterminant growth habits for ratoon cotton (Gossypium spp.) cropping. Issue 1 (16th December 2020) - Zhang, Xin; Kong, Xiangjun; Zhou, Ruiyang; Zhang, Zhiyong; Zhang, Jinbao; Wang, Linsong; Wang, Qinglian
ABSTRACT: Ratoon is the stub or root of a perennial plant that is commonly retained after harvest to produce a following crop. This paper presents a review of ratoon cotton in relation to a broader framework that has been examining perennialization of agriculture for the benefit of ecology and economy. Cotton is botanically indeterminate, but has been treated as an annual after domestication, yet the habit of perenniality is retained and the plants begin to resprout after the first harvest. In some cropping systems, this tendency is exploited using the "ratooning" practice (i.e. growing one or more crops on the rootstock of the first). Ratooning has declined for various reasons such as an increase in the prevalence of pests and diseases and overwintering risk. However, ratooning has many benefits such as no annual tillage before sowing, a well-established root system, and high yield. The three methods of ratooning offer flexibility to balance the environmental and economic benefits in agriculture. The greatest environmental benefits arise from perennial ratoon cropping of semi-wild cotton, and the greatest economic benefit is obtained from biannually cropping modern annual cultivars. However, an optimum solution would be provided by perennial cropping annual cultivars. To realize both environmental and economic benefits, research is needed in the following main areas: preventing the buildup of pests and diseases, breeding the most suitable cotton cultivars for ratooning, and developing light and simplified cultivation (LSC) systems for ratoon cultivation.